Mexican-Hispanic self-employment entry: the role of business start-up constraints - Magnus Lofstrom; Chunbei Wang (Institute for the Study of Labor (IZA), 2006)
This paper examines causes of the low self-employment rates among Mexican-Hispanics by studying self-employment entry utilizing the 1996 panel of the Survey of Income and Program Participation (SIPP). The data show that Mexican-Hispanics are less likely to be self-employed as well as entering self-employment, relative to non-Hispanic whites. Importantly, we analyze self-employment by recognizing heterogeneity in business ownership across industries and show that a classification of firms by human and financial capital intensiveness, or entry barriers, is effective in explaining differences in entrepreneurship across ethnic groups. We show that the lower self-employment entry rates among Mexican-Hispanics are due to lower entry rates into business ownership of firms in relatively high-barrier industries. In fact, Hispanics are more likely to start-up a business in a low-barrier industry than whites.
urn:nbn:de:101:1-2009030969
Keywords: 330